Feasibility of Systemically Applied dsRNAs for Pest-Specific RNAi-Induced Gene Silencing in White Oak - Bragg, Zachary; Rieske, Lynne K. (Frontiers in Plant Science, 2022)
The efficacy of double-stranded RNA (dsRNA) in inducing host specific gene knockdown and mortality has been demonstrated in a multitude of insects and dsRNAs are being integrated for pest suppression in a variety of agricultural and horticultural crops. However, less attention has been applied to their use in forest settings, despite the demonstrated susceptibility of multiple forest pests to RNAi. Prior to implementation for forest pest suppression, characterization of the specificity, efficacy, and behavior of dsRNAs in the environment is essential. Therefore, we investigated the translocation and retention of exogenously applied dsRNA in an economically and ecologically significant hardwood tree when applied hydroponically. White oak (Quercus alba, L.) seedlings were exposed to dsRNAs as a root soak, and at 1, 3, 5, and 7 d post exposure were destructively sampled, divided into stem and leaf tissue, and the RNA extracted. Gel electrophoresis was used to visualize the presence of exogenous dsRNA in treated seedling material and Sanger sequencing was used to further verify recovery of treatment dsRNAs. Both techniques confirmed the presence of the exogenously applied dsRNAs in each tissue type at each sample interval, demonstrating successful uptake and translocation of dsRNAs through white oak tissues. Our findings support root uptake as a viable delivery method for dsRNAs in hardwood seedlings, which could provide single tree protection from selected tree feeding pests or pathogens.